SURGICAL TREATMENT OF LEFT-SIDED CONGENITAL DIAPHRAGMATIC HERNIA - I. I. Lovskaya; M. G. Chepurnoy; G. I. Chepurnoy; V. B. Katsupeev; B. G. Rozin (Медицинский вестник Юга России, 2013)
Purpose: To improve results of surgical treatment of children with left-sided congenital diaphragmatic hernia.Materials and methods: 54 clinical observations were analyzed. Anatomical experiment performed on two corpses of children with hernia and 3 corpses of children without them with infusion red lead in mesenteric arteries. Radiovasograms were made.Results: The authors think that congenital diaphragmatic hernia should be considered as ectopic into the pleural cavity abdominal organs displaced sources of blood supply, arising as a result of fetal malformations. It determines the characteristics of surgical correction of the congenital abnormality, associated with fixing the front edge of the diaphragm in the defect area with X or XI rib, consciously reducing the volume of the pleural cavity, as well as the viscero-abdominal disproportion. In the preoperative preparation of appropriate use of high-frequency oscillatory ventilationof lungs (HFOVL), allows to operation children 4-5 days of age with stable main vital systems of the body. Of the 54 children in the near term after surgery, 4 children died, accounting for 7.4%.Summary: Developed surgical techniques and the use of preoperative HFOVL have reduced the mortality rate to near 0.